Entre critique kantienne et critique marxiste - Camilla Brenni (Recherches Germaniques)
This article highlights the insufficient acknowledgment of Hegel’s philosophy in Sohn-Rethel’s attempt to found a materialist epistemology upon a synthesis of Kant’s theory of knowledge and Marx’s critique of political economy. Taking into account Hegel’s contribution to the field of epistemology could have circumvented certain contradictions and incoherencies that arguably emerge in Sohn-Rethel’s theoretical endeavor. This article proposes to examine in detail Hegel’s approach to the concept of abstraction, but also two aspects of his critique of Kant – specifically with regard to the methodological separation of form and content. It thereby intends to present a critique of Sohn-Rethel’s project by highlighting one of its missing links.